2010
DOI: 10.1089/dia.2009.0130
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Pump Therapy in Moslem Patients with Type 1 Diabetes During Ramadan Fasting: An Observational Report

Abstract: Fasting during Ramadan is feasible in patients with type 1 diabetes using an insulin pump, with adequate counseling and support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 15 publications
2
54
1
Order By: Relevance
“…Our findings are similar to the findings of other studies (2)(3)(4) in that the majority of patients with T1D could fast 15 or more days during Ramadan. Nonetheless, symptomatic hypoglycemia was reported and resulted in breaking the fast in 15% of the days.…”
supporting
confidence: 92%
“…Our findings are similar to the findings of other studies (2)(3)(4) in that the majority of patients with T1D could fast 15 or more days during Ramadan. Nonetheless, symptomatic hypoglycemia was reported and resulted in breaking the fast in 15% of the days.…”
supporting
confidence: 92%
“…Two small observational studies reported that patients taking ultralente or insulin lispro could fast without experiencing severe hypoglycaemic episodes [61,62]. More recent studies in patients using insulin pumps reported no cases of severe hypoglycaemia, although some episodes of hypoglycaemia required the fast to be broken and adjustments to the basal rate were needed [63,64]. If patients with T1DM insist on fasting, then the recommended adjustments to insulin medication and/or dosing regimen during Ramadan are outlined in Fig.…”
Section: Adults With T1dmmentioning
confidence: 99%
“…Insulin pumps used in carefully selected educated type-1 diabetics could be very effective in enabling them to fast safely in Ramadan. [3132] Insulin: Type 2 diabetics in good health, with reasonably good diabetic control and free from advanced complications, and requiring insulin alone or in combination with oral medications, may undertake Ramadan fasting. Generally speaking, long acting basal insulin is advised at Iftar times, and supplemented by short-acting insulin at Suhur times.…”
Section: Strategies To Ensure Safety Of Diabetics Who Plan To Fastmentioning
confidence: 99%